La filosofía del lenguaje en Wittgenstein y la cuestión del lenguaje privado - Sergio Iván Vera Ortiz (Ciencia Ergo Sum)
This paper examines Wittgensteins discussions about the concept of private language. Wittgenstein rejects the possibility of existence of private language, by virtue of all language being social. Arguments arising from his philosophical investigations are examined and the importance of Wittgensteins ideas for contemporary thought is emphasized.